Let's analyze each step of Emeril's solution.
-
Combine like terms: 4b + 2b - 3 = -21
- The combination of like terms is done correctly: \(4b + 2b = 6b\).
- This gives: 6b - 3 = -21 (This step is correct.)
-
Subtraction property of equality: 6b = -24
- To isolate \(6b\), Emeril subtracts \(3\) from both sides. However, on the left side, he should have added \(3\) to both sides.
- The correct operation would be: \[ 6b - 3 + 3 = -21 + 3 \implies 6b = -18. \]
- Thus, this step contains an error.
-
Subtraction property of equality: b = -4
- Emeril divided \(-24\) by \(6\) to get \(b = -4\), but since the previous equation was incorrect, this step is also incorrect.
To summarize, the error occurred in Step 2, where Emeril incorrectly applied the operation of subtraction instead of addition. Therefore, the correct answer is:
Step 2: He should have added 3 to, rather than subtracting 3 from, both sides.